INFLUENCE OF PE TEACHERS' QUALIFICATIONS ON THE MOTOR ABILITIES OF EARLY SCHOOL-AGE CHILDREN - Robert Podstawski; Krzysztof Borysławski (Physical Education of Students, 2014)
Purpose : The aim of the study was to determine the differences in 7-9-year-old children’s motor abilities based on the qualifications of their elementary school P.E. teachers. Material : The two groups of teachers analyzed were graduates of the faculty of physical education and sports science (fully qualified physical education teachers) and those of the faculty of pedagogy, specialized in early education (early education teachers). The studies were conducted in 12 elementary schools in northeastern Poland and involved a group of 1,205 7-9-year-old students. Eleven motor tests were used to adequately assess the levels of the children's motor abilities. Results : The study results confirmed that teaching qualifications influence motor abilities of children of both sexes although, more significantly in boys, which may stem from their higher ecosensitivity. Conclusions : The highest number of significant differences between the results of individual motor trials occurred among third graders, with students of fully qualified teachers achieving better results. This may be connected with the longer period of participating in well-thought-out P.E. lessons